How Historical Sociology Can Be Taken and How Then It Should Be Practiced - D. Yu. Karasev (Социология власти)
The essay presents its author's understanding of historical sociology, as well as a view on how to practice historical sociology. The preconditions that have been necessary for the emergence of historical sociology from the American intellectual tradition are the following: first, to overcome the 'historiosophical ahistoricism' of classical sociology and the ahistoricism of early empirical sociology in the United States. Second, the emergence of 'social history' in Europe under the influence of the Great War and the social sciences rejecting the idea of progress in its evolutionary and revolutionary interpretations. The essay provides a detailed investigation of the features of the 'new historical science' in comparison with its traditional counterpart, as well as exploring the similarities and differences between social history and historical sociology. Social history is considered as an intermediate link between the classical 'sociology of history' and American historical sociology. Following social history, historical sociology turns to comparative studies and quantitative methods, but at the same time does not abandon hermeneutics. Historical sociology presupposes a mutual weakening of the nomothetics of classical 'grand theories' and the ideography of traditional history. It also implies a full-fledged sociological investigation of historical phenomena using procedures accepted in empirical sociology, rather than the reinterpretation of historical research in sociological-theoretical terms. This results in the emergence of special (rather than general) processual and medium-level theories of social change based on historical facts. Historical sociology focuses on theoretical generalizations, which clearly distinguishes it from social history. The essay investigates the different approaches and purposes of using the comparative historical method — and the quantitative methods that complement it. In turn, their utilization leads to problems with the acceptance of their results by traditional historians specialized in a single country and on studying primary sources in the original. Instead of concluding, the author discusses his experience and participation in the institutionalization of historical sociology in Russia and points out the problems hindering it.